2020
DOI: 10.1111/resp.13806
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of e‐cigarette vaping on pulmonary function and airway inflammation in healthy individuals and in patients with asthma

Abstract: Background and objective The acute effects of e‐cigarettes have not been scientifically demonstrated yet. The aim of this study was to assess the acute changes in pulmonary function and airway inflammation in patients with asthma after vaping one e‐cigarette. Methods Twenty‐five smokers suffering from stable moderate asthma according to GINA guidelines with no other comorbidities and 25 healthy smokers matched with the baseline characteristics of the asthmatic patients were recruited. PFT, IOS, FeNO and EBC we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…Even if exposure to e‐cigarette is less harmful than tobacco smoking among patients with asthma, 5 e‐cigarette may be a harmful smoking cessation tool compared to other nicotine replacement therapies. Although some authors did not find any acute effects of vaping on lung function in asthmatic patients, 10 others found that exposure to vaped nicotine e‐liquid induces an acutely obstructive pattern 6,9,11 of higher magnitude and longer duration compared to healthy smokers 8 . This bronchoconstriction may negatively affect the response to bronchodilation therapy and facilitates symptom aggravation and acute exacerbations 1,2,12 …”
Section: Article Methods Main Results Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if exposure to e‐cigarette is less harmful than tobacco smoking among patients with asthma, 5 e‐cigarette may be a harmful smoking cessation tool compared to other nicotine replacement therapies. Although some authors did not find any acute effects of vaping on lung function in asthmatic patients, 10 others found that exposure to vaped nicotine e‐liquid induces an acutely obstructive pattern 6,9,11 of higher magnitude and longer duration compared to healthy smokers 8 . This bronchoconstriction may negatively affect the response to bronchodilation therapy and facilitates symptom aggravation and acute exacerbations 1,2,12 …”
Section: Article Methods Main Results Conclusionmentioning
confidence: 99%
“…In a recent publication in Respirology , Kotoulas et al . evaluated the effects of acute e‐cigarette vaping with nicotine on lung function and airway inflammation among a randomized controlled trial group of 25 smokers with well‐controlled moderate asthma, and 25 healthy smokers matched for age, gender, body mass index and the number of pack‐years of cigarette consumption 6 . In asthmatic smokers, vaping e‐cigarette leads to an acute, significant decrease in the peak expiratory flow (−7.8%), an increase in airway impedance at 5 Hz (Z5Hz) (+7.6%) and in airway resistance at 10 and 20 Hz (R10Hz and R20Hz, respectively).…”
Section: Article Methods Main Results Conclusionmentioning
confidence: 99%
“…Studies assessing short-term health effects of ENDS use suggest that, although less harmful than traditional cigarettes, users still experience respiratory symptoms (Osei et al, 2019;Schweitzer et al, 2017;Wang et al, 2018;Wills et al, 2019). Furthermore, those with preexisting asthma may suffer more immediate health effects, such as reduced pulmonary function and airway inflammation, compared to those without asthma (Kotoulas et al, 2020). After adjusting for other covariates, we found that there was an increase in the odds of asthma for those who use e-cigarettes that were quite similar to that for combustible cigarettes, although the association was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies where FeNO significantly decreased after an EC session [ 45 ], whereas the opposite result was exhibited in another study [ 47 ]. In the latter study, Th2 cytokines such as interleukins (IL) IL-4 and IL-13 in the EBC of asthmatics were found to be significantly increased after vaping for five minutes, reflecting increased eosinophilic inflammation, and supporting the finding of increased FeNO [ 47 ]. Apart from Th2 inflammatory mediators, an increase in IL-1β and tumor necrosis factor alpha (TNF-α) was observed.…”
Section: Resultsmentioning
confidence: 93%
“…Mean airway resistance along with the slope of the phase III curve on the single breath nitrogen test increased immediately after short-term EC use in a group of asthmatic smokers, thereby demonstrating airway dysfunction, particularly in small airways [ 46 ]. Apart from airway resistance, asthmatic patients also exhibited impaired pulmonary function tests (PFTs) after vaping for five minutes, with the decrease in forced expiratory volume in 1 s to forced vital capacity ratio (FEV1/FVC) and peak expiratory flow (PEF) being more significant [ 47 ]. Furthermore, patients who recovered from electronic vapor acute lung injury (EVALI), a condition more commonly observed in asthmatic patients, exhibited chronic irreversible airflow obstruction, markedly abnormal 129 Xe MRI ventilation heterogeneity, abnormal lung clearance index and oscillometry measures and decreased diffusing capacity of the lung for carbon monoxide (DLCO), all persistent after their discharge [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%